Digital Political Branding dan Agenda-Setting dalam Pemilihan Presiden Indonesia 2024: Analisis Kampanye Prabowo-Gibran - Lubis, Muhammad Ridwan; Dianto, Icol (Jurnal Pendidikan dan Dakwah, 2025)
This research is motivated by the dominance of digital campaigns in the 2024 Indonesian Presidential Election and the need to understand how the construction of candidate images through personal branding and visual strategies affects the behavior of young voters. This study analyzes Prabowo-Gibran's political marketing strategy through four main elements: image transformation through personal digital branding "gemoy", the use of TikTok as a medium for visual and emotional campaigns, the strategy of segmenting Generation Z and millennial voters, and the integration of media and non-media strategies to expand political reach. The methods used include literature studies and content analysis of social media uploads, short videos, slogans, and netizens' interactions. The results showed that "gemoy" branding reproduced through visual symbols, humor, and aesthetics of popular culture effectively built psychological closeness with young voters. TikTok serves as an arena for spreading messages based on virality, fast rhythm, and algorithmic engagement that strengthens Prabowo's framing as a light and familiar figure. Face-to-face campaigns and social programs are reproduced as digital content thus expanding the resonance of the message. These findings confirm that the success of the Prabowo–Gibran campaign was driven by a hybrid campaign model that combines digital and non-digital strategies in shaping the preferences of young voters. This research contributes to the study of political marketing by demonstrating the role of personal, emotional branding and algorithmic logic, and recommending the optimization of hybrid campaign strategies for upcoming elections.   Penelitian ini dilatarbelakangi oleh dominasi kampanye digital dalam Pemilihan Presiden Indonesia 2024 dan kebutuhan memahami bagaimana konstruksi citra kandidat melalui personal branding serta strategi visual memengaruhi perilaku pemilih muda. Penelitian ini menganalisis strategi pemasaran politik Prabowo–Gibran melalui empat elemen utama: transformasi citra melalui personal branding digital “gemoy”, pemanfaatan TikTok sebagai medium kampanye visual dan emosional, strategi segmentasi pemilih Generasi Z dan milenial, serta integrasi strategi media dan nonmedia untuk memperluas jangkauan politik. Metode yang digunakan mencakup studi literatur dan analisis konten terhadap unggahan media sosial, video pendek, slogan, dan interaksi warganet. Hasil penelitian menunjukkan bahwa branding “gemoy” yang direproduksi melalui simbol visual, humor, dan estetika budaya populer efektif membangun kedekatan psikologis dengan pemilih muda. TikTok berfungsi sebagai arena penyebaran pesan berbasis viralitas, ritme cepat, dan engagement algoritmik yang memperkuat pembingkaian Prabowo sebagai figur ringan dan akrab. Kampanye tatap muka dan program sosial diproduksi ulang sebagai konten digital sehingga memperluas resonansi pesan. Temuan ini menegaskan bahwa keberhasilan kampanye Prabowo–Gibran didorong oleh model kampanye hibrida yang menggabungkan strategi digital dan nondigital dalam membentuk preferensi pemilih muda. Penelitian ini berkontribusi pada kajian pemasaran politik dengan menunjukkan peran personal branding emosional dan logika algoritmik, serta merekomendasikan optimalisasi strategi kampanye hibrida untuk pemilu mendatang.